Triage of Women with Low-Grade Cervical Lesions : HPV mRNA Testing versus Repeat Cytology - Sørbye, Sveinung Wergeland; Arbyn, Marc; Fismen, Silje; Gutteberg, Tore Jarl; Mortensen, Elin (PLoS ONE, 2011)
In Norway, women with low-grade squamous intraepithelial lesions (LSIL) are followed up after six months in order to decide whether they should undergo further follow-up or be referred back to the screening interval of three years. A high specificity and positive predictive value (PPV) of the triage test is important to avoid unnecessary diagnostic and therapeutic procedures. At the University Hospital of North Norway, repeat cytology and the HPV mRNA test PreTect HPVProofer, detecting E6/E7 mRNA from HPV types 16, 18, 31, 33 and 45, are used in triage of women with ASC-US and LSIL. In this study, women with LSIL cytology in the period 2005–2008 were included (n = 522). Two triage methods were evaluated in two separate groups: repeat cytology only (n = 225) and HPV mRNA testing in addition to repeat cytology (n = 297). Histologically confirmed cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) was used as the study endpoint. Of 522 women with LSIL, 207 had biopsies and 125 of them had CIN2+. The sensitivity and specificity of repeat cytology (ASC-US or worse) were 85.7% (95% confidence interval (CI): 72.1, 92.2) and 54.4 % (95% CI: 46.9, 61.9), respectively. The sensitivity and specificity of the HPV mRNA test were 94.2% (95% CI: 88.7, 99.7) and 86.0% (95% CI: 81.5, 90.5), respectively. The PPV of repeat cytology was 38.4% (95% CI: 29.9, 46.9) compared to 67.0% (95% CI: 57.7, 76.4) of the HPV mRNA test. HPV mRNA testing was more sensitive and specific than repeat cytology in triage of women with LSIL cytology. In addition, the HPV mRNA test showed higher PPV. These data indicate that the HPV mRNA test is a better triage test for women with LSIL than repeat cytology.